2021
DOI: 10.3389/fphar.2021.670389
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Reduces Endothelial Dysfunction and Apoptosis Induced by High-Fat Diet and Palmitate in Thoracic Aortas and Endothelial Cells via ROS-ER Stress-CHOP Pathway

Abstract: Macrovascular disease is tightly associated with obesity-induced metabolic syndrome. Sitagliptin (SIT), an orally stable selective inhibitor of Dipeptidyl peptidase-4 (DPP-4), has protective effects on endothelium. However, the mechanisms enabling SIT to exhibit resistance to diet-induced obesity (DIO) related with reactive oxygen species (ROS) and endoplasmic reticulum (ER) stress in the aorta and endothelial cells have not been reported yet. Therefore, the present study was conducted to determine if SIT exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 87 The drug works by reducing cell death in liver cells, decreasing fat production in the liver, and managing oxidative stress and related inflammation. 88 In one clinical trial, researchers explored the effectiveness of combining sitagliptin with insulin glargine for treating NAFLD in T2DM patients, comparing it to the combination of liraglutide and metformin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 87 The drug works by reducing cell death in liver cells, decreasing fat production in the liver, and managing oxidative stress and related inflammation. 88 In one clinical trial, researchers explored the effectiveness of combining sitagliptin with insulin glargine for treating NAFLD in T2DM patients, comparing it to the combination of liraglutide and metformin.…”
Section: Resultsmentioning
confidence: 99%
“…DPP-4 inhibitors like Sitagliptin and SGLT2 inhibitors such as Tofogliflozin showcase the intertwined pathophysiology of NAFLD and T2DM, underscoring the potential benefits these antidiabetic agents might confer on hepatic steatosis and inflammation. 84 , 88 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the STZ model induces a Type I diabetes state of severe hyperglycemia, our HFD model increased blood glucose by approximately 20%, yet this may be sufficient to drive AR-dependent effects in the endothelium. A previous study showed that only 2 weeks of HFD feeding in young male C57BL/6J (WT) mice induced endothelial cell insulin resistance [44], perhaps due to increased circulating fatty acids such as palmitate [45]. How AR contributes to the earliest deleterious changes in endothelial cells that give rise to ED under HFD feeding remains both a mystery and a potential therapeutic target [15].…”
Section: Discussionmentioning
confidence: 99%
“…2 Endothelial dysfunction can be induced by vascular injury, such as stent implantation. Preexisting vascular diseases, especially atherosclerosis, 3 hypertension, 4 diabetes, 5 and some other conditions, including cigarette smoking, 6 alcohol, 7 high fat diet, 8 and aging, 9 which can accelerate endothelial dysfunction. Dysfunction of endothelium is characterized by not only alternation of morphology and motility but also changes in endothelial behaviors, including an imbalance in the relative contribution of endothelium-derived relaxing and contracting factors, 10 disrupted vascular tone, 11 increased vascular permeability-induced inflammatory reactions, 3 which contributes to regulate development of thrombus formation, 12 atherosclerosis, 3 vascular restenosis, 13 arterial aneurysm, 14 and arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%